Objective assessment, repeatability, and agreement of shoulder ROM with a 3D gyroscope - El-Zayat, Bilal Farouk; Efe, Turgay; Heidrich, Annett; Anetsmann, Robert; Timmesfeld, Nina; Fuchs-Winkelmann, Susanne; Schofer, Markus Dietmar (BMC musculoskeletal disorders, 2013)
Background Assessment of shoulder mobility is essential for diagnosis and clinical follow-up of shoulder diseases. Only a few highly sophisticated instruments for objective measurements of shoulder mobility are available. The recently introduced DynaPort MiniMod TriGyro ShoulderTest-System (DP) was validated earlier in laboratory trials. We aimed to assess the precision (repeatability) and agreement of this instrument in human subjects, as compared to the conventional goniometer. Methods The DP is a small, light-weight, three-dimensional gyroscope that can be fixed on the distal upper arm, recording shoulder abduction, flexion, and rotation. Twenty-one subjects (42 shoulders) were included for analysis. Two subsequent assessments of the same subject with a 30-minute delay in testing of each shoulder were performed with the DP in two directions (flexion and abduction), and simultaneously correlated with the measurements of a conventional goniometer. All assessments were performed by one observer. Repeatability for each method was determined and compared as the statistical variance between two repeated measurements. Agreement was illustrated by Bland-Altman-Plots with 95% limits of agreement. Statistical analysis was performed with a linear mixed regression model. Variance for repeated measurements by the same method was also estimated and compared with the likelihood-ratio test. Results Evaluation of abduction showed significantly better repeatability for the DP compared to the conventional goniometer (error variance: DP = 0.89, goniometer = 8.58, p = 0.025). No significant differences were found for flexion (DP = 1.52, goniometer = 5.94, p = 0.09). Agreement assessment was performed for flexion for mean differences of 0.27° with 95% limit of agreement ranging from −7.97° to 8.51°. For abduction, the mean differences were 1.19° with a 95% limit of agreement ranging from −9.07° to 11.46°. Conclusion In summary, DP demonstrated a high precision even higher than the conventional goniometer. Agreement between both methods is acceptable, with possible deviations of up to greater than 10°. Therefore, static measurements with DP are more precise than conventional goniometer measurements. These results are promising for routine clinical use of the DP.